HUMAN SACRIFICES LIMA ASSOCIATED WITH LAST CONSTRUCTIVE STAGE OF HUACA PUCLLANA - Barreto, María Inés (2010)
The results presented here are part of the Project of Investigation, Conservation, and Enhancement of the Huaca Pucllana directed by Dra. Isabel Flores Espinoza, with the guidance of the National Institute of Culture and the City of Miraflores. The remains of two individuals were found during the 2007 and 2009 excavation seasons in Huaca Pucllana, in part of the construction fill used as a base for the fifth platform built during The Middle Horizon 1B. In this context we observe two forms of burial. One was on a bed of canes with offerings while the second was only wrapped in a textile bundle. The analysis of the excavation, of the bones and the textiles permits the suggestion that both individuals were sacrificed at the same time as part of rituals related to the modification of the architectonical structure.